Biogas-to-biomethane upgrading: A comparative review and assessment in a life cycle perspective. (April 2021) - Ardolino, F.; Cardamone, G.F.; Parrillo, F.; Arena, U.
Abstract: The study reviews and compares the most utilised techniques to obtain high quality biomethane by upgrading biogas from anaerobic digestion of the organic fraction of municipal solid waste. Environmental and economic aspects of membrane separation, water scrubbing, chemical absorption with amine solvent, and pressure swing adsorption have been quantified in a life cycle perspective. An attributional environmental Life Cycle Assessment has been implemented with the support of a Material Flow Analysis and in combination with a complementary environmental Life Cycle Costing. The analyses are based on data largely obtained from Italian existing plants but they can be generalised to the whole European Union, as demonstrated by a companion sensitivity analysis. The comparative assessment of the results indicates all the examined options as fully sustainable, also identifying the "win-win" situations. In particular, the membrane separation technique appears to have the best performances, even though in some cases with limited differences. With reference to base case scenarios, this technique shows better results for the respiratory inorganics potential (up to 34%, i.e. up to 328 kgPM2.5eq /y), global warming potential (up to 7%, i.e. up to 344 tCO2eq /y), and non-renewable energy potential (up to 12%, i.e. up to 6400 GJprimary /y) as well as for life cycle costs (up to 3.4%, i.e. about 60 k€/y). The performances of the examined techniques appear anyway dependent on site-specific conditions (such as the injection pressure in the gas grid or the existence/amount of local economic incentives) and commercial strategies for the market of interest. Highlights: Environmental and economic impacts of biogas upgrading units have been assessed. Life Cycle Assessment and Life Cycle Costing have been used as analytical tools. All examined techniques imply a reduction of environmental and economic impacts. Win-win situations indicate some advantages for membrane separation technique. Site-specific conditions and market strategies affect upgrading technique selection.